Analysis and Design of Web-Based Mobile Library Services from an Economic Perspective - Aminudin; Egi Abinowi; Khansa Nurul Andini; Resti Dewi Sri; Haliatul Aulia Dzulfiqor (SAFE-Network, 2024)
A library is an institution or institution that provides a collection of written, printed and recorded library materials as a central source of information which is regulated according to standard systems and rules and utilized for educational purposes, research, information dissemination and intellectual recreation for the community. In modern life, libraries need to provide accurate and equitable information services to the entire community, not only around regional library buildings, whether in Provincial/Regency/City Libraries but also to communities whose residences are far from the reach of library buildings. So that people in these areas can enjoy information services to increase their knowledge, libraries must be in their environment. To build a library building requires quite a lot of money, so to overcome this, the Bandung City Archives and Library Service provides suitable facilities, namely the Mobile Library. A mobile library is a library where reading materials are carried around from one place to another, services to the community are carried out directly in the place where the mobile library is located. The aims of this research are to analyze the needs for mobile library service website features; Find out visitor reports and the distribution of areas visited by Disarpus using graphs. The research stages that will be carried out include an initial survey, determining the problem formulation, determining research methods, data processing and analysis, and creating a final report.